Comprehensive Behavior Management : Individualized, Classroom, and Schoolwide Approaches. - Martella, Ronald C. C. (SAGE Publications, 2011)
Comprehensive Behavior Management: Schoolwide, Classroom, and Individualized Approaches supports teachers in preventing management problems and responding to unwanted behavior when it occurs in classrooms. The text offers a comprehensive presentation of three levels of behavior management strategies: individual, classroom, and schoolwide, all three of which contribute to a positive learning environment. A social learning emphasis in which human behavior is viewed within an ecological framework is integrated throughout the text. Application of this information is supported by a range of pedagog.